2016
DOI: 10.21569/2222-7415-2016-6-2-60-71
|View full text |Cite
|
Sign up to set email alerts
|

11c-Choline Pet/Ct in Recurrence Detection in Surgically Treated Prostate Cancer Patients With Low Psa Level

Abstract: ель исследования. Изучить возможности позитронно-эмиссионной томо-графии, совмещенной с компьютерной томографией (ПЭТ/КТ) с 11 С-Холином у больных РПЖ с низкими значениями ПСА (<2,0 нг/мл) после радикальной простатэктомии.Материалы и методы. Проанализированы результаты 63 ПЭТ/КТ исследований с 11 С-Холином; среднее значение ПСА составило 0,94±0,51 (0,21-1,98) нг/мл, медиана -0,93 нг/мл. Сканирование выполнялось на гибридной системе «Biograph-64» True Point PET/CT (Siemens) через 10 минут после внутривенного вв… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Though, PET/CT was able to detect PCa relapse in 43% (50/115) patients with low PSA values (< 2 ng/ml). According to data of other authors, PET/CT showed corresponding rates ranged from 19% to 55% [9,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 77%
“…Though, PET/CT was able to detect PCa relapse in 43% (50/115) patients with low PSA values (< 2 ng/ml). According to data of other authors, PET/CT showed corresponding rates ranged from 19% to 55% [9,19,[21][22][23][24].…”
Section: Discussionmentioning
confidence: 77%